Different indicators for postprocedural mitral stenosis caused by single- or multiple-clip implantation after percutaneous mitral valve repair. Issue 4 (April 2018) - Itabashi, Yuji; Utsunomiya, Hiroto; Kubo, Shunsuke; Mizutani, Yukiko; Mihara, Hirotsugu; Murata, Mitsushige; Siegel, Robert J.; Kar, Saibal; Fukuda, Keiichi; Shiota, Takahiro
Highlights: Postprocedural mitral stenosis (MS) is a main limitation of MitraClip™ procedure. The preprocedural predictors of postprocedural MS were detected in our study. Mitral orifice area predicted the postprocedural MS after 1-clip implantation. Mitral annular diameter predicted the postprocedural MS after 2-clip implantation. The number of implantable clips could be predicted before procedure using our data. Abstract: Background: Postprocedural mitral stenosis (MS) is a main limitation for MitraClip™ (Abbot Vascular, Inc., Santa Clara, CA, USA) procedure. The purpose of this study was to detect the preprocedural predictors of high transmitral pressure gradient (TMPG) after MitraClip™ implantation, which indicated postprocedural mitral stenosis (MS). Methods: We studied 79 patients who were implanted with MitraClip™ in our institute. Before the procedure, mitral valve orifice area (MVOA), and anterior–posterior (AP) and medial-lateral (ML) mitral annular diameters were measured at diastole using three-dimensional (3D) transesophageal echocardiography (TEE) data set. After the procedure, the mean TMPG was assessed using continuous-wave (CW) Doppler by periprocedural TEE. Results: Preprocedural MVOA, and AP and ML diameter of left ventricular (LV) inflow orifices were larger in patients with mean TMPG ≤4 mmHg than in patients with TMPG >4 mmHg after 1-and 2-clip implantation. The large MVOA and ML diameter of LV inflow orifice strongly correlated with the low TMPG after 1- and 2-clip implantation. As a result of the receiver operating characteristic curve analysis, the preprocedural MVOA predicted the low postprocedural TMPG more accurately than the ML diameter of LV inflow orifice after 1-clip implantation either in the degenerative or functional mitral regurgitation (MR) patients. After 2-clip implantation, however, the preprocedural ML diameter of LV inflow orifice predicted it more accurately than the MVOA in the degenerative and functional MR patients. Conclusions: 3D TEE derived MVOA predicts the postprocedural MS after 1-clip implantation, however, preprocedural ML diameter of LV inflow orifice is more useful to predict after 2-clip implantation.